The ethnobotany of the Tsonga-Shangana in selected areas of Bushbuckridge in the Bohlabela District of the Limpopo Province - Shilubane, Paul Xilavi (University of Limpopo, 2008)
In this study, the multidisciplinary epistemology of ethnobotany is reviewed within the wider context of ethnoecology and indigenous knowledge systems. The major problems derived from this theoretical framework cover aspects of the relationship between cultural groups and their natural environment - particularly the botanical component of the latter. Problems and critical questions about this relationship were investigated in selected areas of the Bushbuckridge district, which are inhabited by a number ofTsonga-Shangana communities. Salient aspects of the natural habitat in the study area are discussed with special reference to the vegetation, climate and soil types. A proper understanding of the culturally-based exploitation of plant resources necessitates a sound knowledge of the culture concerned, including relevan t aspects of its value-system and cosmology. In this review, emphasis is placed on those aspects of culture that are directly concerned with the utilisation of plant resources. The latter include a wide range of economic, technological and medicinal uses. Specimens of 200 plants were collected and identified by the University of Limpopo Herbarium. The uses of every species are described. Systematised tables of plant uses are presented, as well as comparative lists in which selected uses are compared to those of other cultures in which the same species are used. The effects of plant utilisation, as well as indigenous forms of resource management, are also discussed. Recommendations are made on how to counter the process of environmental degradation which is caused by over-exploitation .
Thesis (PhD. (Anthropology)) --University of Limpopo, 2008
Keywords: Ethnobotany; Tsonga-Shangana; Ethnobotany--South Africa; Plants,useful--South Africa